The essential moral self - Strohminger, Nina; Nichols, Shaun (Cognition, 2014)
•Not all parts of the mind contribute equally to judgments of personal identity.•Memory and distinguishing features contribute less to identity than moral traits.•Moral traits are the strongest contributor to identity, the self, and the soul. It has often been suggested that the mind is central to personal identity. But do all parts of the mind contribute equally? Across five experiments, we demonstrate that moral traits—more than any other mental faculty—are considered the most essential part of identity, the self, and the soul. Memory, especially emotional and autobiographical memory, is also fairly important. Lower-level cognition and perception have the most tenuous connection to identity, rivaling that of purely physical traits. These findings suggest that folk notions of personal identity are largely informed by the mental faculties affecting social relationships, with a particularly keen focus on moral traits.